2006
DOI: 10.3732/ajb.93.8.1140
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics of the florally diverse Andean clade Iochrominae (Solanaceae)

Abstract: Recent molecular phylogenetic studies of Solanaceae have identified many well-supported clades within the family and have permitted the creation of a phylogenetic system of classification. Here we estimate the phylogeny for Iochrominae, a clade of Physaleae sensu Olmstead et al. (1999), which contains 34 Andean species encompassing an immense diversity of floral forms and colors. Using three nuclear regions, ITS, the second intron of LEAFY, and exons 2 to 9 of the granule-bound starch synthase gene (waxy), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
131
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(143 citation statements)
references
References 53 publications
11
131
1
Order By: Relevance
“…In Solanaceae, initial phylogenetic studies detected 29 only one copy of the GBSSI gene, such as in the diploid Solanum (Levin et al, 2006; 30 Peralta and Spooner, 2001), the Iochrominae group of the tribe Physaleae (Smith and Baum, 2006), Schizanthus (Perez et al, 2006), and Nolana's close 1 relative Lycieae (Levin and Miller, 2005). In a recent study, more than two copies of 2 this gene were found in Hyoscyameae, a polyploid group from the northern hemisphere 3 closely related to Nolana (Yuan et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Solanaceae, initial phylogenetic studies detected 29 only one copy of the GBSSI gene, such as in the diploid Solanum (Levin et al, 2006; 30 Peralta and Spooner, 2001), the Iochrominae group of the tribe Physaleae (Smith and Baum, 2006), Schizanthus (Perez et al, 2006), and Nolana's close 1 relative Lycieae (Levin and Miller, 2005). In a recent study, more than two copies of 2 this gene were found in Hyoscyameae, a polyploid group from the northern hemisphere 3 closely related to Nolana (Yuan et al, 2006).…”
mentioning
confidence: 99%
“…The first use of LEAFY for phylogenetic study of Solanaceae 13 (Smith and Baum, 2006) All 63 species analyzed in our previous GBSSI study (Dillon et al 2007) followed Olmstead and Sweere (1994), Shaw et al (2005) and Shaw et al (2007), 13 respectively. The primers trnC (5'-CCAGTTCAAATCCGGGTGTC-3') and 2039R…”
mentioning
confidence: 99%
“…Combined phylogenetic analyses from three nuclear loci, the internal transcribed spacer (ITS), the second intron of LEAFY, and exons 2 to 9 of GBSSI, show that all of the traditional genera, with the exception of Vassobia and the monotypic Acnistus, are not monophyletic (Figure 1; Smith and Baum, 2006). Accordingly, many of the floral characters used to delimit groups appear to be homoplasious.…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on Iochrominae sensu Olmstead et al (1999), a group of Andean Solanaceae whose evolutionary history has recently been clarified using DNA sequence data from three nuclear regions (Smith and Baum, 2006). Using this phylogenetic framework, we here examine the evolution of taxonomically important floral traits and evaluate the potential for hybridization among species distributed across the clade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation